Polymer Encapsulants Incorporating Light‐Guiding Architectures to Increase Optical Energy Conversion in Solar Cells. Issue 8 (22nd December 2017) - Biria, Saeid; Chen, Fu Hao; Pathreeker, Shreyas; Hosein, Ian D.
Abstract: The fabrication of a new type of solar cell encapsulation architecture comprising a periodic array of step‐index waveguides is reported. The materials are fabricated through patterning with light in a photoreactive binary blend of crosslinking acrylate and urethane, wherein phase separation induces the spontaneous, directed formation of broadband, cylindrical waveguides. This microstructured material efficiently collects and transmits optical energy over a wide range of entry angles. Silicon solar cells comprising this encapsulation architecture show greater total external quantum efficiencies and enhanced wide‐angle light capture and conversion. This is a rapid, straightforward, and scalable approach to process light‐collecting structures, whereby significant increases in cell performance may be achieved. Abstract : Broadband waveguide array architectures are inscribed into polymer films as a new encapsulant material for solar cells. The architectures are grown in a binary‐component, photocurable resin through light‐induced self‐writing, which elicits spontaneous formation of the core–cladding waveguide profile. Their light‐collecting and light‐guiding functions are inherited by the film, thereby enabling large‐scale enhanced and wide‐angle optical energy collection and conversion.